Karakteristik Oleogel dari Campuran Minyak Sawit dengan Minyak Kanola dan Konsentrasi Oleogelator Lilin Lebah yang Berbeda - Maria Virginia Myrananda Myrananda; I Wayan Rai Widarta; Ni Nyoman Puspawati (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Shortening is made through a partial hydrogenation process that can produce trans fatty acid and is at risk of causing cardiovascular diseases. The oleogelation process serves as an alternative to produce oleogels that resemble to shortening. This research aimed to determine the effect of mixing palm oil with canola oil and beeswax concentration on the characteristics of oleogels and identify the ratio of palm oil to canola oil and beeswax concentration that yielded oleogels with the best characteristics. The experimental design employed was a Factorial Completely Randomized Design. The first factor was the mixing ratio of palm oil with canola oil consist of 5 levels: 90:10, 80:20, 70:30, 60:40, and 50:50, while the second factor was the beeswax concentration with 4 levels: 4%, 6%, 8%, and 10%. The treatments were repeated twice, resulting in a total of 40 experimental units. The data are analyzed using Analysis of Variance (ANOVA). If the treatment shows a significant effect, the data are further analyzed using the Duncan Multiple Range Test (DMRT). The data on the iodine number for the optimal oleogel treatment was analyzed using a T-Test. The results show that the mixing ratio of palm oil with canola oil and the beeswax concentration affect the hardness, oil loss, oil loss after 30 days of storage, and color. The oleogel with the best characteristics is obtained from the treatment with a palm oil with canola oil ratio of 50:50 and a beeswax concentration of 10%, with the following characteristics: iodine value of 67.61 g I₂/100g, hardness of 1.68 N, oil loss of 1.15%, oil loss after 30 days of storage of 0.77%, and color values of L* 71.78, a* 15.42, and b* 36.65, indicating a slightly yellowish white color.